2015
DOI: 10.1016/j.seizure.2014.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Perceived stigma in Korean adolescents with epilepsy: Effects of knowledge about epilepsy and maternal perception of stigma

Abstract: The knowledge that the AWE had about their epilepsy, maternal concealment behavior, and receiving polytherapy were significantly related to the AWE's perception of stigma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(17 citation statements)
references
References 26 publications
(50 reference statements)
0
16
0
1
Order By: Relevance
“…In Thailand, survey participants from an urban area had better knowledge, attitudes, and practices toward people with epilepsy than those from a nonurban area . Related to the perception of stigma in adolescents with epilepsy, a Korean survey showed that low knowledge level and maternal concealment behavior were important predictors of higher stigma perception …”
Section: Psychosocial Diagnostic and Treatment Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…In Thailand, survey participants from an urban area had better knowledge, attitudes, and practices toward people with epilepsy than those from a nonurban area . Related to the perception of stigma in adolescents with epilepsy, a Korean survey showed that low knowledge level and maternal concealment behavior were important predictors of higher stigma perception …”
Section: Psychosocial Diagnostic and Treatment Challengesmentioning
confidence: 99%
“…74 Related to the perception of stigma in adolescents with epilepsy, a Korean survey showed that low knowledge level and maternal concealment behavior were important predictors of higher stigma perception. 75 Despite different attitudes between Asian and Western countries, stigmatization still occurs in the West. In a European survey, 10% of participants had negative attitudes toward epilepsy, which mostly occurred in people with low socioeconomic background, low theoretical knowledge of epilepsy, misconceptions of epilepsy as a form of insanity, and no personal contact with a person with epilepsy.…”
Section: Stigmatizationmentioning
confidence: 99%
“…Furthermore, negative attitudes on the part of family and friends, in addition to difficulties in interpersonal relationships, are factors that perpetuate stigma in society. The are asmost affected by epilepsy observed in this study relate to difficulties at work, at school, and in social interactions, activity restriction and negative feelings by patients (18).…”
Section: Discussionmentioning
confidence: 64%
“…As a result, knowledge of epilepsy can minimize the impact of perceived stigma, depressive feelings, and anxiety. This trial indicated also that correlation between the level of the maternal concealment behavior and adolescent with epilepsy's perception of stigma was more significant than maternal knowledge of epilepsy or maternal perception of stigma [67].…”
Section: Stigmamentioning
confidence: 82%